Analysis of Rice Consumer Loyalty in Pekanbaru City - Chezy WM Vermila; Andi Alatas (Publisher Cv. Inara, 2021)
This study aims to determine the loyalty of consumers who buy rice in Pekanbaru City. The method used is the survey method for households in Pekanbaru City, which consists of 12 Districts which are divided proportionally based on BPS data in 2020. The sample in this study is 240 households, based on the field survey results obtained for consumer characteristics are at 84.00% of the productive age ranges from 15 - 35 years old. For educational characteristics, 63.41% of undergraduate consumer education (S1) covers various fields of science. Then for the characteristics of income, it is found that as much as 6.92% of consumer income is 2,888,564 or equivalent to MSEs. Whereas for the type of work obtained as many as 57.4% have a livelihood / job as private employees. Meanwhile, the results of the analysis of consumer loyalty are not yet at the level of loyal buyers because the loyalty pyramid value of Switcher buyers is still above 50% and the value of committed buyers is still very small, namely 26.67%. The level of loyalty of rice consumers in the city of Pekanbaru is not yet at the level of loyal buyers because in the loyalty pyramid the value of Switcher buyers is still above 63%, which is 56.61% with the frequent category and the committed buyer value is also very small, namely 49.72% with the non-category. like, for the value of Liking The Brand and Satisfied Buyer, which is 100% with the very satisfied category. And the Habitual Buyer value is 96.66% with the category agree.